Entre o ritmo, a cor e o movimento: as territorialidades na festa de congada da cidade de Ituiutaba/MG - Rafael, Luana Regina Mendes (2018)
The present work has as its theme the territoriality of the Saint Benedict's festivity in the city of Ituiutaba, from 1950 to 2017. Ituiutaba is located in the Triângulo Mineiro region, Minas Gerais state. The objective of this investigation was to understand the territorial dynamics present in the festival of congada of the city of Ituiutaba. Specifically, it was aimed to understand the territorial dynamics in the origin of the party in the city of Ituiutaba; (des) territorialization and (re) territorialization in the context of socio-spatial relations of the festivities of St. Benedito, on the occasion of the prohibition of the celebration of the feast of St. Benedito in the center of the city of Ituiutaba; and to study the territoriality of the festivities in the present time, as well as the conflicts resulting from the appropriation of the territory in the place of the party and its surroundings.We propose as initial questions to think: How was the process of passing the festive celebration near the Mother Church to the small chapel of St. Benedict built in a peripheral region? How did people feel? And what is the role of the Church from the changes that have been motivated by social impositions like the revelers appropriated territory of Saint Benedict? How was the space reorganized? In addition, what are the new conflicts? Originated in the aspirations of the humanity Sciences, qualitative research arose as a possibility of a methodological pathway that would meet more precisely the specificitiess of social research, approaching the essence of behaviors. In this context, in the first chapter we look at the concept of territory, responsible for grounding the discussions about the congada party based on Cultural Geography. In the second, we approach the spaces that the popular festivals occupy; for this, I tried to understand the parties as a spatial phenomenon. To broaden our discussion about the congada party we have established a reflection on the territorial identities of the popular festivals. In the third chapter, the discussion had as central question to think about the congada party in the city of Ituiutaba, trying to understand the rural origins of this party. At this time of the research we will understand the public space that was denied to the congadeiros. As specified in the specific objectives, this research intends to think about the processes of (de) territorialization, (re) territorialization. In this third chapter, we will try to think of 13 de Maio Square as the space where the party is (re) territorialized in the urban space of the city of Ituiutaba. Finally, in the fourth chapter we will think about the party from the new territorial dynamics of the party today, as well as the new conflicts and perspective for the future that the party assumes in the present.